ENERGY EFFICIENCY ACHIEVEMENT STUDY BY COMPENSATING REACTIVE POWER IN MINING ENTERPRISES (Ustozlar uchun, 2025)
In mining enterprises, reactive power is mainly achieved through capacitor batarekas when compensing. Obtaining reactive power from the network will lead to an increase in electricity consumption on the network. Electricity consumption today causes significant economic damage. One of the associ consumers of reactive power is asynchronous electric motors.